Canning Process Tuna (Canned Tuna) with High Temperatures in PT. Aneka Tuna Indonesia, Pasuruan - I Made Satya Widnyana; Hari Suprapto (Journal of Marine and Coastal Science, 2019)
Tuna is one of the main export commodities from Indonesia. Indian Ocean has the potential of large pelagic fish resources among them include tuna amounting to 386.260 tonnes per year with a production of 188.280 tons per year and the utilization rate of 48.74%. The purpose of this field practice is to acquire additional knowledge, experience and skills in the process of canning tuna with high temperatures in the PT. Aneka Tuna Indonesia, Pasuruan. This field practice was held in PT. Aneka Tuna Indonesia, Jl. Surabaya-Malang Km. 38 Desa Gempol, Kecamatan Gempol, Kabupaten Pasuruan, East Java at January 18th until February 19th, 2015. the practice used descriptive method and took data with primary and secondary data. The data retrieved from observation, interview, active participation, and literature review. Products canned tuna was originally derived from the receipt of raw materials tuna, then do the grouping size of each type of fish, included cold storage, wash or do thawing, cutting or cutting, then cooked or cooking, done showering or fish cooling, after that is done pre cleaning and cleaning, do metal detecting, and subsequent filling of meat, charging medium, closing cans or seaming, sterilization, incubated (stored in warehouses), performed labeling and packaging, and finally collected into containers or stuffing.